Unveiling pre-service teachers’ cognitions of multilingualism and multilingual identities using a multi-method approach - Henehan, Alison (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2024)
Teacher cognitions of multilingualism influence classroom behaviour and are partly formed during pre-service teacher (PST) education (Borg 2003). In Fryslân, a linguistically diverse region of the Netherlands, Frisian is a compulsory subject, yet teachers feel underprepared to teach it, leading to negative attitudes towards the minority language and multilingualism in general. A survey, dominant language constellation (DLC) artefacts (Ibrahim 2022), and focus groups with vignettes (Barter & Renold 1999) were used to explore 72 PSTs’ cognitions of multilingualism in education and multilingual identities. Our triangulation of methods shows how cognitions of multilingualism can be mapped in various ways. PSTs held slightly positive cognitions of multilingualism in education in the survey and identified as multilingual in the DLCs and focus groups. However, PSTs’ cognitions of minority languages should be improved. This study contributes to the understanding of PSTs’ multilingual identities and cognitions and offers guidance on how the concept of teacher cognition can be applied to multilingualism to improve training on multilingual pedagogies for PSTs.
Keywords: dominant language constellations; dominantne jezikovne konstelacije; manjšinski jeziki; minority languages; multilingual identity; multilingual teacher education; pre-service teachers; stališča učiteljev; študenti pedagogike; teacher cognition; večjezična identiteta; večjezično izobraževanje učiteljev